Suppressive Effect of Everolimus on IL-2, IL-10, IL-21, and IFNγ Levels: Implications for the Successful Minimization of Calcineurin Inhibitor Use in Transplantation. Issue 3 (June 2019) - Iwasaki, Kenta; Kitahata, Nana; Miwa, Yuko; Uchida, Kazuharu; Matsuoka, Yutaka; Horimi, Kosei; Kobayashi, Takaaki
Abstract : Background: Success with calcineurin inhibitors (CNIs) such as cyclosporine A (CSA) and tacrolimus (TAC) in organ transplantation has demonstrated that cytokine suppression is a key factor in patient management. However, the exact effects of recently introduced immunosuppressive agents other than CNI on cytokine expression remain unknown. In this study, the action of the mTOR-inhibitor everolimus (EVR) and that of the antimetabolite mycophenolic acid (MPA) on the transcription of several cytokines was investigated. Methods: Peripheral blood mononuclear cells obtained from healthy volunteers were stimulated with anti-CD3/28 microbeads in the presence of CSA, TAC, EVR, and/or MPA for 8 hours. The mRNA levels of each cytokine were measured using quantitative real-time polymerase chain reaction. Results: MPA had no inhibitory effect on any of the cytokines tested. EVR showed moderate inhibition of IL-2, IL-10, IL-21, and IFNγ levels. These cytokines were further analyzed to investigate the additive effect of EVR in combination with CNI. The beneficial effect of EVR addition was seen at low concentrations of CSA or TAC, while no additive effect was observed at high concentrations. Conclusions: EVR might effectively inhibit the activation of recipient immune cells in combination with a low dose of CNI, maximizing clinical benefit by preventing graft rejection and alleviating CNI-induced adverse effects. Abstract : Supplemental Digital Content is Available in the Text.